SISTEM PAKAR SISTEM PAKAR DENGAN METODE FORWARD CHAINING UNTUK DIAGNOSA GEJALA COVID-19 - Juwanto muksoni; Ari Syaripudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Right now, the world is being rocked by a great pandemic called Covid-19 (Corona Virus Disease). The increase from day to day in the number of patients infected with the Covid-19 virus is already difficult to control. A clear and straightforward plan is needed from the government to tackle this problem (Wahidah et al., 2020). Covid-19 is one of the most dangerous and number one killing viruses in the world today and cannot be handled properly. COVID-19 is caused by SARS CoV 2 and was first discovered in Wuhan, China. This virus can cause mild respiratory infections to severe respiratory infections. The infection can occur through droplets or splashes of saliva from one person to another when coughing or sneezing. The World Health Organization (WHO) has announced that this virus can be transmitted between humans (human to human transmission) and become an epidemic throughout the world. (Aprilia et al., 2021). By using an expert system combining inference rules with a certain knowledge base provided by one or more experts in a particular field. Conceptually, the user (user) conveys facts or information to expert system and then receive advice from experts or expert answers. The inside of the expert system consists of two main components, namely the knowledge base which contains knowledge and the inference engine that describes the conclusions. The Forward Chaining method is a search method or forward tracking technique that starts with existing information and combines rules to produce a conclusion or goal. The process is repeated until a result is found. With the rapid antigen swab test and PCR, we can find out our current condition. If the result is positive for COVID-19, then we can immediately take steps to protect the people around us. If the result is negative, we still have to be vigilant and discipline the protocol 3M health.